Creating a bigger ZPD by extending learning process via online forum - Hussin, Supyan (Universiti Utara Malaysia, 2007)
Formal learning usually takes place in a four wall classroom. An extension of learning process may continue to occur in a conventional setting where learners get together physically after class hours. In other words, learning may take place within particular zones. Vygotsky’s idea of zone of proximal development (ZPD) suggests that learning may not only take place within a prescribed zone but also outside the prescribed zone. The prescribed zone usually has a set of objectives to be achieved by the learners. However, during the learning process, some learners may learn and/or acquire more knowledge or skills beyond targeted objectives if there is room for them to do so. The non-prescribed zone is determined by the learners’ own initiatives and efforts. With the advancement of internet technology, learners are now able to extend their learning/acquisition process via online forum. This paper will describe how learners viewed online forum activity that was used in two separate classes for two consecutive semesters at a local university. It will also discuss some pedagogical principles in implementing online forum in courses and a few implications that need to be considered by policy makers, teachers/instructors, and ICT coordinators.